2019
DOI: 10.1111/jan.14035
|View full text |Cite
|
Sign up to set email alerts
|

Mental health patients’ experiences of softer coercion and its effects on their interactions with practitioners: A qualitative evidence synthesis

Abstract: Aims To synthesize qualitative evidence of mental health patients’ treatment‐related experiences of softer coercion and its effect on their interactions with practitioners. Background Coercion is controversial but global in mental health care. It ranges from softer to harder forms, but less attention is given in the literature to softer coercion. Design Qualitative thematic synthesis examining patients’ experiences of softer coercion. Data Sources Electronic databases searched from inception to September 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(150 reference statements)
0
13
0
Order By: Relevance
“…Chapter 3 consists of an adapted published article: (Allison and Flemming, 2019) CHAPTER 1: Introduction In her above quote, Bella strikes at the heart of the debilitating experience of voice hearing for many people, especially for those entering mental health services for treatment. Voice hearing is about relationships.…”
Section: Author's Declarationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapter 3 consists of an adapted published article: (Allison and Flemming, 2019) CHAPTER 1: Introduction In her above quote, Bella strikes at the heart of the debilitating experience of voice hearing for many people, especially for those entering mental health services for treatment. Voice hearing is about relationships.…”
Section: Author's Declarationmentioning
confidence: 99%
“…As I go on to discuss in Chapter 3, it became evident from the evidence synthesis that coercion is a much-debated phenomenon, broadly defined across mental healthcare, and negatively affecting patients' treatment experiences and subsequent distress. In my published article of this evidence synthesis, I found that practitionerpatient relationships within mental health treatment environments can be undermined by imbalances of power, typically illustrated through a range of coercion, and described by patients in traumatic terms (Allison and Flemming, 2019).…”
Section: Voice Hearing Mental Healthcare and Coercionmentioning
confidence: 99%
“…13 15 Like formal coercion, informal coercion is likely to affect nurse–patient interactions negatively, undermining patients’ autonomy and dignity as well as their trust in caregivers. 4,7,16 However, when the caring relationship is trustful and the nurses know the patient, it is possible to make use of coercion in a more gentle way, thus reducing patients’ experiences of inferiority. 17 One example can be to let the patient choose which nurse should administer a medication that the patient does not want to have.…”
Section: Background and Aimmentioning
confidence: 99%
“…5,6 Examples of such subtle coercion are different actions where caregivers use their power to put pressure on patients to behave in a certain way and comply with treatment plans. This kind of coercion, which has also been described as ‘softer coercion’, 7 is more implicit. As it is not subject to formal decisions and documentation, it could also be described in terms of informal coercion 8,9 which is the term we will use.…”
Section: Introductionmentioning
confidence: 99%
“…Informal coercion may include such things as persuasion, threats to use harder forms of coercion, or undue pressure to comply with treatment (LeFrançois, 2014;Valenti et al, 2015). Although soft coercion may not be explicit or as tangible, it nevertheless enables its application to a wide range of people (e.g., people who are voluntarily hospitalized or cared for), and may be just as harmful, (re)traumatising, and oppressive for those who are subjected to it (Allison & Flemming, 2019;Nyttingnes, Ruud, & Rugkåsa, 2016).…”
Section: Introductionmentioning
confidence: 99%